Multidisciplinaty treatment in a child with dentigerous cyst - Alina Rodríguez Castellanos; Mayra Barrera Garcell; Humberto Manuel Rodríguez Rey (Centro Provincial de Información de Ciencias Médicas, 2021)
The case report of a seven years old child who was referred to Mártires del Moncada Provincial Teaching Stomatological Clinic in Santiago de Cuba, who had a dentigerous cyst and monostotic fibrous displasia is presented. Since then, and almost during 10 years, the patient has been assisted by a multidisciplinary odontopediatric team, which has followed his clinical course and has applied different diagnostic and therapeutic protocols, including surgical procedures, prosthetic rehabilitations, chemotherapy, among others. Due to the case complexity and the frequency with which both clinical entities are associated in childhood, it was decided to publish this work for the national anf foreing odontological community.